2003
DOI: 10.1089/107555303322284802
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAnticancer Activities ofLeonurus heterophyllusSweet (ChineseMotherwort Herb)

Abstract: LHS was able to induce apoptosis of all the tumor cell lines tested. The antiproliferation effect was dose- and time-dependent. The mitochondrion was found to be involved in the apoptosis induced by the LHS extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Tao et al (2009) studied the anticancer effects of the ethanol extract of Leonurus japonicas at the cellular level and their results demonstrated that the ethanol extract caused cell death in a dose-dependent and time-dependent fashion in human breast cancer cells. The anticancer activity of the aqueous extract of the aerial part of Leonurus heterophyllus on MCF-7 and MDA-MB 453 human breast cancer cells was also demonstrated (Chinwala et al, 2003;Mazzio & Soliman, 2009;Tao et al, 2009). However, the effective component of Leonurus heterophyllus is less studied.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Tao et al (2009) studied the anticancer effects of the ethanol extract of Leonurus japonicas at the cellular level and their results demonstrated that the ethanol extract caused cell death in a dose-dependent and time-dependent fashion in human breast cancer cells. The anticancer activity of the aqueous extract of the aerial part of Leonurus heterophyllus on MCF-7 and MDA-MB 453 human breast cancer cells was also demonstrated (Chinwala et al, 2003;Mazzio & Soliman, 2009;Tao et al, 2009). However, the effective component of Leonurus heterophyllus is less studied.…”
Section: Discussionmentioning
confidence: 89%
“…(Labiatae) has been primarily used to treat menoxenia, dysmenorrhea, amenorrhea, lochia, edema of body, oliguresis, sores, ulcerations, and other diseases in women. Recent studies showed that ethanol extract and aqueous extract from Leonurus japonicas present anticancer ability (Chinwala et al, 2003;Li et al, 2011Li et al, , 2013Nagasawa et al, 1990Nagasawa et al, , 1992. Little work has been done to identify the specific compound of the extracts presenting the anticancer ability.…”
Section: Introductionmentioning
confidence: 99%
“…Motherwort (Leonurus japonicus Houtt) is a medicinal herb used in China as a traditional emmenagogue (an agent that promotes menstrual discharge) and an antipyretic and is now known to produce valuable products which have potential application in the treatment of various diseases (9,29,30). However, so far the antimicrobial ingredients in motherwort have been poorly investigated.…”
mentioning
confidence: 99%
“…Among them are Baccharis dracunculifolia [20], Bidens pilosa [21], Chelidonium majus [22], Chenopodium ambrosioides [23], Citrus limon [24], Coffea arabica [25], Curcuma longa [26], C. zedoaria [27], Hypericum perforatum [28], Leonurus sibiricus [29], Malpighia glabra [30], Malva sylvestris [31], Maytenus ilicifolia [32], Mikania hirsutissima [33], Nicotiana tabacum [34], Oenothera biennis [35], Origanum majorana [36], Petiveria alliacea [37], Phyllanthus tenellus [38], Piper tuberculatum [39], Schinus molle [40], S. terebinthifolia [41], Senna obtusifolia [42], Solanum cernuum [43], Stevia rebaudiana [44], Taraxacum officinale [45], Tetradenia riparia [46], Tropaeolum majus [46], Urtica dioica [47], and Vernonia polyanthes [48] (Table 1). Similarly, the carcinogenesis preventive extract of Hibiscus rosa-sinensis [49] also afforded low to moderate values.…”
Section: Discussionmentioning
confidence: 99%